2004
DOI: 10.1136/vr.155.2.52
|View full text |Cite
|
Sign up to set email alerts
|

Retinal dysplasia in wild otters (Lutra lutra)

Abstract: Eyes from 88 otters found dead in south-west England between 1990 and 2000, were collected as part of a larger pathological study. Histopathological examination of 131 eyes revealed dysplastic changes such as rosetting and folding in the retinas of 26 of the otters. In the eyes of 42 of the otters there were postmortem and fixation-induced retinal detachment which complicated the differentiation of dysplastic from normal retina, but 11 eyes had folds which probably indicated a dysplastic pathology. The eyes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
2
1
Order By: Relevance
“…No obvious signs of pathology were noted at post mortem examination, although the two found in 2008 were severely emaciated. A dieldrin concentration associated with retinal dysplasia in otters (339 µg/kg wet weight liver; Williams et al, 2004) was exceeded by 54 otters (7%) found in most years and regions (Figures 1 and 2), however, the eyes of the otters in the current study were not examined. DDT liver residues of 1300 µg/kg in female mink have been associated with physiological effects such as increased embryonic loss and altered kit sex ratio (Gilbert, 1969); this threshold was exceeded in 31 otters (4%) which were found across most years (1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008) and from the Midlands, Anglian, North East and Wales regions (Figures 1 and 2).…”
Section: Potential Health Effects: Toxic Thresholds and Reproductive Statuscontrasting
confidence: 58%
“…No obvious signs of pathology were noted at post mortem examination, although the two found in 2008 were severely emaciated. A dieldrin concentration associated with retinal dysplasia in otters (339 µg/kg wet weight liver; Williams et al, 2004) was exceeded by 54 otters (7%) found in most years and regions (Figures 1 and 2), however, the eyes of the otters in the current study were not examined. DDT liver residues of 1300 µg/kg in female mink have been associated with physiological effects such as increased embryonic loss and altered kit sex ratio (Gilbert, 1969); this threshold was exceeded in 31 otters (4%) which were found across most years (1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008) and from the Midlands, Anglian, North East and Wales regions (Figures 1 and 2).…”
Section: Potential Health Effects: Toxic Thresholds and Reproductive Statuscontrasting
confidence: 58%
“…However, microscopic examination of the eyes is a helpful aid in diagnosis of vitamin A deficiency. Williams et al 34 documented many cases of retinal dysplasia in free-ranging European otters (Lutra lutra) with low hepatic retinol concentrations. This vitamin A deficiency was linked to high tissue burdens of polychlorinated biphenyls (PCBs), which are capable of antagonizing liver vitamin A stores.…”
Section: Discussionmentioning
confidence: 98%
“…Retinal dysplasia has been described in all domestic species, though dogs are the most frequently affected (NARFSTRÖM; PETERSEN-JONES, 2013). Among nondomestic species, the condition has been described in otters (WILLIAMS et al, 2004) and in one hawk specimen (DUKES;FOX, 1983). To our knowledge, there are no reports in wild carnivore species.…”
Section: Introductionmentioning
confidence: 90%